W trybach wojennej gospodarki. Bydgoskie wystawy żywieniowe, hodowlane i tekstylne w okresie I wojny światowej (Kronika Bydgoska, 2021)
When Bydgoszcz was annexed by Prussia, it was a major production and trade center, which starting from 1855 had organized prominent economic exhibitions (industrial, craft, agricultural, culinary, horticultural, etc.), attracting exhibitors also from outside the Poznań Province. An unusual market situation after the outbreak of World War I had also an impact on the change of profile and range of trade shows organized in Bydgoszcz. Exhibitions of this type became prominent local events, focusing on issues that were related directly to the daily life of residents. Their main target was to educate people in the scope of intensification of animal husbandry (small animals such as goats and rabbits) in family-run farms, preparation of substitute meals and purchase of inexpensive clothing. These exhibitions played an important role in daily urban life, serving not only as entertainment, but also a significant factor in the process of adjustment to a new, wartime reality.